1999
DOI: 10.1002/(sici)1099-1166(199904)14:4<272::aid-gps896>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Wandering behaviour in community-residing persons with dementia

Abstract: Objectives To examine wandering behaviour in elderly demented persons in the community setting with respect to dementia characteristics and other factors that might influence wandering behaviour; to generate a statistical model to assess the relative importance of these various factors in predicting wandering behaviour. Design Cross‐sectional, case‐control investigation. Setting University‐affiliated outpatient neuropsychiatric assessment center. Participants Six hundred and thirty‐eight consecutive community‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 36 publications
6
119
1
4
Order By: Relevance
“…Nighttime wandering behaviors have been reported especially in male PD patients with severe cognitive decline living in nursing homes [24]. It is also typical for severe Alzheimer's disease [25]. Bliwise et al [26] reported an even higher frequency of disruptive nocturnal behaviors in PD than in AD.…”
Section: Sleepwalking and Parkinson's Disease: Prevalencementioning
confidence: 99%
“…Nighttime wandering behaviors have been reported especially in male PD patients with severe cognitive decline living in nursing homes [24]. It is also typical for severe Alzheimer's disease [25]. Bliwise et al [26] reported an even higher frequency of disruptive nocturnal behaviors in PD than in AD.…”
Section: Sleepwalking and Parkinson's Disease: Prevalencementioning
confidence: 99%
“…Wandering is a common characteristic of dementia, occurring in around 15-60% of those who are diagnosed with the illness, [1][2][3][4] with a diverse incidence found in both communitydwelling and institutionalised patients. It is often grouped together with other psychological and behavioural problems occurring in dementia.…”
Section: Background Description Of the Underlying Problemsmentioning
confidence: 99%
“…The participants included in the review were people with acute or chronic cognitive impairment, of any age, who exhibited wandering behaviour 1,2,4,8 including people:…”
Section: Types Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, at the behavioral level, AD is not only a matter of cognitive dysfunction. The disease is also associated to noncognitive manifestations such as restlessness, wandering, aggressiveness, agitation, etc (eg Klein et al, 1999;Meguro et al, 2004;Profenno and Tariot, 2004). It is therefore tempting to make a parallel between the hyperactivity found in EC + SAPO rats and restlessness or increased ambulation in demented or AD patients.…”
Section: The Combination Of Ec and 192 Igg-saporin Lesionsmentioning
confidence: 99%